Seismic Behaviour and Retrofit of Historic Masonry Minaret - Coşgun, Cumhur; TÜRK, AHMET MURAT (My University, 2012)
The dynamic behaviour of block masonry minaret of a historical mosque in Istanbul is analyzed, and a seismic retrofit method is proposed. Due to high seismicity of the region, a 3D finite element model is used to determine lateral displacements and failure modes under seismic load. The analyses show that the highest damage usually occurs at the base and the lower part of the minaret, and that lateral behaviour can be improved by strengthening these sections with fiber reinforced polymer (FRP) sheets. The results obtained are promising in terms of seismic protection.